Ampliación del concepto de refugiado: el caso de Venezuela y los desplazados ambientales (2020)
The refugee protection regime in international law was created as a consequence of the phenomenon of mass migrations, particularly from those resulting from different armed confrontations. However, at present there are different causes for large movements of people, which are driving us to rethink the classic concept of ‘refugee’ based on persecution due to race, religion, nationality, social group, and political opinions. The impossibility to develop their life in dignified conditions in their country of nationality raises as an object of discussion and study the situation of the so-called economic migrants and environmentally displaced persons, understood as possible cases of expansion of the refugee concept and whose study is the main objective of this article. The research method used was the theoretical-deductive one, because the development of the article started with the general understanding of the concept of refugee to later analyze those specific cases of mass migrations that, based on doctrinal positions and reality itself, are the basis of the proposal to broaden the refugee concept. A general conclusion is that, although the classical conception of refugee would not allow the inclusion of other people in similar conditions, there are new realities that are generating large mass migrations that should be analyzed in order to obtain protection in equal conditions, as in the case of economic migrants and environmentally displaced persons. The research presented allows us to contribute to the debate on the necessary reforms in some of the most important and traditional regulations of international law in application of the principles of cooperation and solidarity.